2016
DOI: 10.7824/rbh.v15i4.487
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de glyphosate na dessecação do sorgo biomassa

Abstract: O sorgo biomassa é uma alternativa para a geração de energia renovável pela queima em caldeiras, destacando-se por sua alta produtividade e possibilidade de mecanização de todos os seus processos agrícolas. Uma alternativa comum para a redução da umidade de culturas é a aplicação de herbicidas dessecantes, contudo, não há pesquisas que elucidem a perda de umidade da massa colhida de sorgo com a aplicação de dessecantes na parte aérea, antes da colheita. Assim, o objetivo deste trabalho foi avaliar aplicação de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Our results corroborate those found by May et al (2016) who evaluated the application of four doses of glyphosate (0, 720, 1,440, 2,160 and 2,880 g a.i. ha -1 ) in greenhouse biomass sorghum after 7, 14, 21 and 28 days after application.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results corroborate those found by May et al (2016) who evaluated the application of four doses of glyphosate (0, 720, 1,440, 2,160 and 2,880 g a.i. ha -1 ) in greenhouse biomass sorghum after 7, 14, 21 and 28 days after application.…”
Section: Resultssupporting
confidence: 91%
“…Several studies have already demonstrated the efficiency of pre-harvest desiccation in soybean (Pinto et al, 2016), beans (Silva et al, 2017), rice, canola (Zhang & Van Vekdhuizen, 2016) and wheat (Krenchinsk et al, 2017). However, there are few research records that have evaluated the application of pre-harvest herbicides to reduce moisture in biomass crops and there are no published studies that have evaluated the effect of herbicides in desiccation of biomass sorghum (Costa et al, 2018;May et al, 2016). In this sense, the objective was to evaluate the use of herbicides in pre-harvest of biomass sorghum for moisture removal and their effect calorific power.…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate is found in several formulations, all of which have the same mechanism of action, but varying regarding the salts that compose it (May et al, 2016). Isopropylamine, ammonium, and potassium stand out among these salts, which have no herbicidal activity, but they are converted into an acidic form with herbicidal activity when absorbed by the plant (D'Amato, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The herbicide glyphosate is widely used for desiccating different plant species, including those for straw formation in the no-tillage system (May et al, 2016;Santos et al, 2016;Timossi et al, 2016). Among its characteristics are the low cost, fast degradation, broad spectrum of action, and low toxicity to mammals.…”
Section: Introductionmentioning
confidence: 99%